Bio-inspired in situ crosslinking and mineralization of electrospun collagen scaffolds for bone tissue engineering. (October 2016) - Dhand, Chetna; Ong, Seow Theng; Dwivedi, Neeraj; Diaz, Silvia Marrero; Venugopal, Jayarama Reddy; Navaneethan, Balchandar; Fazil, Mobashar H.U.T.; Liu, Shouping; Seitz, Vera; Wintermantel, Erich; Beuerman, Roger W.; Ramakrishna, Seeram; et al.
Abstract: Bone disorders are the most common cause of severe long term pain and physical disability, and affect millions of people around the world. In the present study, we report bio-inspired preparation of bone-like composite structures by electrospinning of collagen containing catecholamines and Ca 2+ . The presence of divalent cation induces simultaneous partial oxidative polymerization of catecholamines and crosslinking of collagen nanofibers, thus producing mats that are mechanically robust and confer photoluminescence properties. Subsequent mineralization of the mats by ammonium carbonate leads to complete oxidative polymerization of catecholamines and precipitation of amorphous CaCO3 . The collagen composite scaffolds display outstanding mechanical properties with Young's modulus approaching the limits of cancellous bone. Biological studies demonstrate that human fetal osteoblasts seeded on to the composite scaffolds display enhanced cell adhesion, penetration, proliferation, differentiation and osteogenic expression of osteocalcin, osteopontin and bone matrix protein when compared to pristine collagen or tissue culture plates. Among the two catecholamines, mats containing norepinephrine displayed superior mechanical, photoluminescence and biological properties than mats loaded with dopamine. These smart multifunctional scaffolds could potentially be utilized to repair and regenerate bone defects and injuries.